Self-determined motivation profiles among undergraduate students: A robust test of profile similarity as a function of gender and age - Litalien, D.; Gillet, N.; Gagné, Marylène; Ratelle, C.; Morin, A. (Pergamon, 2019)
This study examines profiles of undergraduate students defined based on their types of behavioral regulation, as proposed by self-determination theory, as well as the similarity of these academic motivation profiles as a function of gender and age. This research also documents the implications of these profiles for students’ vitality and investigates the role of maternal and paternal involvement, autonomy support, and warmth in predicting profile membership. A total of 1072 undergraduate students participated in this study (Mage = 22.7 years; 58.4% female). To test for profile similarity, participants were divided into three age categories. Latent profile analyses revealed five distinct motivation profiles: Knowledge-Oriented, Controlled, Multifaceted, Unmotivated, and Hedonist profiles. These profiles, as well as their associations with the covariates, were similar across gender and age groups. Students’ level of vitality varied across profiles and was higher in the Hedonist and Knowledge-Oriented profiles, whereas both parents’ warmth predicted membership in profiles characterized by high levels of intrinsic motivation.